Madrasah dan Ujian Nasional - Supa’at, Supa’at (Nadwa, 2013)
This research analysis the implication of the policy of the national final exams (Ujian Nasional-UN) in basic to high school that conducts every year by the government, the ministry of education and culture. This researchnot discussabout the validity of UN as government policy, butthe main focus of this research is the implication of UN to madrasah as Islamic education ins-titution that has unique and different character from general school. AsIslamic education,curriculum of madrasah based on the Islamic teachings which the sublime behavior as the final objective of Islamic education. In reality, the policy of UN has caused madrasah to become trapped in prac-tical efforts to help student pass by focusing on repetitive practice of test in examination subject.The defication of test scores and the application of the policy standardization have result in the process education causing fear in students, teachers, and madrasah management. Finaly, students experient stress and depressiondue to fear of failing the UN.